Оновлення трудового законодавства в контексті запровадження самостійних форм роботи: дистанційної та надомної - Клименко, А. Л.; Klymenko, A. L.; ORCID https://orcid.org/0000-0001-9587-5827 (Право і безпека. - 2021. - № 1 (80). - С. 144-150, 2021)
Досліджено передумови та напрямки вдосконалення правового регулювання дистанційної роботи. Уточнено сутність і зміст двох самостійних видів (форм) роботи – дистанційної та надомної – в контексті змін вітчизняного трудового законодавства (законопроєкт № 4051: статті 60-1 та 60-2). Розкрито інституційну природу понять «remote work», «teleworking», «telecommuting», «work from home» з позиції міжнародного досвіду. Охарактеризовано механізм організації дистанційної та надомної роботи, зокрема розкрито характерні ознаки, адаптаційний механізм, зобов’язання та обов’язки сторін, особливості вимірювання продуктивності праці працівників. Обґрунтовано раціональні підходи, з огляду на поточний стан справ на ринку праці та в економіці України, до найбільш коректного трактування цих норм обома сторонами – працівниками та роботодавцем – задля мінімізації будь-яких непорозумінь і ризиків.

The preconditions and directions of improving legal regulation of telecommuting have been studied. The author has found out the specifics of the legal nature of the concepts of “work from home” and “telecommuting” in terms of the approach to the possibilities of various forms of labor organization and labor relations regarding the events related to the pandemic (COVID-19) and consequences for the Ukrainian labor market. Based on the application of general and special methods of scientific cognition, the author has clarified the essence and has expanded the content of two independent types (forms of work): telecommuting and work from home in the context of amendments in domestic labor legislation (draft Law No. 4051: Articles 601 and 602). The institutional nature of the concepts of “remote work”, “teleworking”, “telecommuting”, “work from home” from the standpoint of international experience has been revealed. It has been concluded that work from home is considered more sustainable concept, while telecommuting is remote work from anywhere, with a flexible schedule. It has been clarified that the term of “work from home” in the context of the pandemic (COVID-19) is used in the legislation of a number of foreign countries to denote only remote work at home as a temporary alternative workplace. The author has characterized the mechanism of the organization of telecommuting and work from home according to the draft Law No. 4051, in particular, the author has revealed characteristic features, adaptation mechanism, obligations and responsibilities of the parties, features of measuring the productivity of employees. Based on studying the experience of foreign countries in matters of legislative provision of telecommuting (Austria, the Netherlands, Poland, USA) and the practice of domestic companies, it has been concluded that the home workplace is nothing more than an “extension” or “superstructure” of the employer’s workspace within the organization of the work from home. The author has substantiated the rational approaches based on the current state of affairs at the labor market and in the economy of Ukraine regarding the most correct interpretation of these norms by both parties – employees and the employer to minimize any misunderstandings and risks. Given the risks of the external environment as a possible danger, it has been suggested an in-depth rethinking of approaches to legal support for the work from home and telecommuting, taking into account international practice and recommendations of the International Labor Organization. The emphasis has been placed on the need to find alternative solutions that are in the plane of social responsibility of the employer in matters of protecting labor rights of employees and the prevention of any discrimination.

Исследованы предпосылки и направления совершенствования правового регулирования дистанционной работы. Уточнены сущность и содержание двух самостоятельных видов (форм) работы – удаленной и надомной – в контексте изменений отечественного трудового законодательства (законопроект № 4051: статьи 60-1 и 60-2). Раскрыта институциональная природа понятий «remote work», «teleworking», «telecommuting», «work from home» с позиции международного опыта. Охарактеризован механизм организации дистанционного и надомного труда, в частности раскрыты характерные черты, адаптационный механизм, обязательства и обязанности сторон, особенности измерения производительности труда работников. Обоснованы рациональные подходы с учетом текущего состояния дел в экономике Украины, в частности на рынке труда, к наиболее корректной трактовке данных норм обеими сторонами ‒ работниками и работодателем ‒ для минимизации любых недоразумений и рисков.
Обновление трудового законодательства в контексте внедрения самостоятельных форм работы: дистанционной и надомной
Updating labor legislation in the context of introducing independent forms of work: telecommuting and work from home
Клименко А. Л. Оновлення трудового законодавства в контексті запровадження самостійних форм роботи: дистанційної та надомної / Анастасія Леонідівна Клименко // Право і безпека. - 2021. - № 1 (80). - С. 144-150. - DOI: 10.32631/pb.2021.1.20.
Клименко, А. Л. (2021) «Оновлення трудового законодавства в контексті запровадження самостійних форм роботи: дистанційної та надомної», Право і безпека, 80(1), с. 144-150. doi: 10.32631/pb.2021.1.20.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; трудове законодавство; трудові відносини; нетипові форми зайнятості; дистанційна робота; надомна робота; робоче місце; трудовое законодательство; трудовые отношения; нетипичные формы занятости; удаленная работа; надомная работа; рабочее место; labor legislation; labor relations; atypical forms of employment; telecommuting; work from home; workplace